"We don't have the infrastructure to support them at home": How health system inadequacies impact on long-term care admissions of people with dementia. Issue 12 (December 2017) - Donnelly, Nora-Ann; Humphries, Niamh; Hickey, Anne; Doyle, Frank
Highlights: Health system factors are critical to nursing home placement in dementia. Irish community care services are constrained following the recession. These services are also inequitable. Such limits in community care increases acute hospital admissions in dementia. These acute hospital admissions can accelerate long-term care admissions. Abstract: Objectives: The influence of healthcare system factors on long-term care admissions has received relatively little attention. We address this by examining how inadequacies in the healthcare system impact on long-term care admissions of people with dementia. This is done in the context of the Irish healthcare system. Methods: Thirty-eight qualitative in-depth interviews with healthcare professionals and family carers were conducted. Interviews focused on participants' perceptions of the main factors which influence admission to long-term care. Interviews were analysed thematically. Results: The findings suggest that long-term care admissions of people with dementia may be affected by inadequacies in the healthcare system in three ways. Firstly, participants regarded the economic crisis in Ireland to have exacerbated the under-resourcing of community care services. These services were also reported to be inequitable. Consequently, the effectiveness of community care was seen to be limited. Secondly, such limits in community care appear to increase acute hospital admissions. Finally, admission of people with dementia to acute hospitals was believed to accelerate the journey towards long-term care. Conclusions: Inadequacies in the healthcare system are reported to have a substantial impact on the threshold for long-term care admissions. The findings indicate that we cannot fully understand the factors that predict long-term care admission of people with dementia without accounting for healthcare system factors on the continuation of homecare.